Global relations of production without countervailing power? Possibilities and restrictions to global political economy and the formation of counter-power – using the example of apparel industries - Hurch, Nepomuk (Momentum Quarterly, 2016)
The present article discusses global societal structures, constellations of power and processes of change behind the persistence of exploitation of labour in the apparel industry. It raises the following questions: What strategies of action can be pursued by political economy in this context? What challenges are faced by the consolidation of global countervailing power? The apparel industry is particularly suitable to analyze these matters, since the development of its modes of production and their consequences are a reflection of wider processes of change within the world economy. Here the consequences of neoliberal politics can be traced in a demonstrative manner. Additionally it is a sector, in which international unions and social movements are engaged at the forefront for a more just and social global society.
Keywords: Apparel Industry; Globalization; Neoliberalism; Political Economy; Countervailing Power; Workers Unions